Dual-functional titanium implants via polydopamine-mediated lithium and copper co-incorporation: synergistic enhancement of osseointegration and antibacterial efficacy - Li, Jun; Jiang, Bo; Yang, Liu; Zhang, Pu; Wu, Jingwen; Yang, Yalan; Yang, Yan; Wang, Guiling; Chen, Jie; Zhang, Ling; Huang, Shiqin; Zhang, Lingli; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionOrthopedic implant failure due to inadequate osseointegration and infection remains a critical challenge. To address this, we engineered a polydopamine (PDA)-mediated dual-functional platform for lithium (Li+) and copper (Cu2+) co-incorporation on titanium alloy (Ti6Al4V) implants, aiming to synergize osteogenic and antibacterial properties through a scalable surface modification strategy.MethodsPDA coatings were polymerized onto polished Ti64 substrates, followed by sequential immersion in LiCl (800 μM) and CuCl2 (10 μM) solutions to construct Li+/Cu2+ co-doped surfaces (PDA@Li 800-Cu 10). In vitro assays assessed MC3T3-E1 pre-osteoblast proliferation (CCK-8), osteogenic differentiation (ALP activity, RT-PCR for ALP/Axin2), and antibacterial activity against S. aureus and E. coli (live/dead staining, CFU assays). In vivo efficacy was evaluated in a rat femoral defect model via micro-CT and histology.Results and discussionLi+-functionalized surfaces (PDA@Li 800) enhanced osteoblast proliferation and osteogenesis via Wnt/β-catenin activation. Cu2+-loaded coatings (PDA@Cu 10) eradicated >99% bacteria but moderately suppressed osteogenic markers. The dual-doped PDA@Li 800-Cu 10 surface resolved this bioactivity conflict, maintaining antibacterial efficacy comparable to PDA@Cu 10 while elevating the osteogenic capacity of Cu2+-only modified surfaces. In vivo, dual-modified implants eliminated bacterial colonization within 72 h and significantly increased peri-implant bone volume (BV/TV) in comparison to Ti64 controls, outperforming PDA-only counterparts. By harmonizing Li-driven osteoinduction and Cu-mediated bactericidal action through a scalable PDA platform, this work advances a transformative strategy for next-generation orthopedic and dental implants, simultaneously addressing infection risks and bone regeneration demands.